ANALISIS PENDAPATAN DAN KELAYAKAN FINANSIAL USAHA PENGGEMUKAN SAPI DI KECAMATAN BANJARSARI KELURAHAN METRO UTARA KOTA METRO (STUDI KASUS DI PT SUPERINDO UTAMA JAYA) - Aris Chrisdianto; Sudarma Widjaya; Teguh Endaryanto (Lampung University, 2021)
This study aim is to analyze the income and financial viability of the beef cattle fattening business. This research uses a case study method conducted at PT Superindo Utama Jaya in Banjarsari Village North Metro Subdistrict Metro District, which determined purposively with the consideration that PT Superindo Utama Jaya is a beef cattle fattening center that contributes to the fulfillment of animal protein needs. Data collection was carried out in February - March 2019. In accordance with the results of the analysis beef cattle fattening business is feasible to be cultivated. Sensitivity analysis result with the assumption of decrease in cattle production and selling price of cattle by 11.22 percent and increase in cattle feed costs by 20.19 percent that the fattening business is still feasible to run.Key words: cattle fatening, financial viability, income